The Parental Competence and Resilience Scale for mother and fathers in at-risk psychosocial contexts - Martín, Juan C.; Cabrera, Eduardo; León, Jaime; Rodrigo, María J. (Anales de Psicología / Annals of Psychology, 2013)
This paper describes the development of a scale to assess parental competence and resilience in psychosocial risk contexts. The research was conducted with 63 professionals from the Gran Canaria social services, (Canary Islands, Spain) over 498 cases of at-risk families. The factor structure was obtained by Exploratory Structural Equation Modeling (ESEM) with oblimin rotation, and the estimation method using the Weighted Least Squares with moving measurement window (WLSMW) for confirmatory purposes. The mothers scale showed a structure of five factors with 44 items: Personal Development and Resilience, Household Organization, Seek of Support, Educational Competence, and Community Competence. These factors showed good internal consistency (ordinal alpha ranging from .70 to .97). The fathers scale consisted of 4 factors with 32 items: Personal Development and Resilience, Educational and Household Organization Competence, Community Competence, Seek of support. These factors showed good internal consistency with ordinal alpha ranging from .68 to .97. The results suggested that the questionnaire, in its double version for mothers and fathers, captures the specificities of each parental role and showed sound psychometric properties that make it suitable for the social services field.